Growth of REBa2Cu3Ox single-crystal whiskers utilizing the concept of high-entropy alloys. (1st March 2023) - Suzuki, Yasunori; Nagao, Masanori; Maruyama, Yuki; Watauchi, Satoshi; Tanaka, Isao
Abstract: Single-crystal whiskers of RE Ba2 Cu3 O x ( RE -123, RE : rare Earth element) cuprate superconductors were successfully grown using Te-doped precursors utilizing the concept of high-entropy-alloys at the RE site. The obtained whiskers were 0.5–1.0 mm in length with approximately 10 μ m thickness. The width of the flat surface, which corresponds to the ab -plane, was 10–50 μ m. The RE site of the grown whiskers could be easily substituted by large ionic radius RE elements (Gd, Dy and Ho). Substitution with small ionic radius RE elements (Tm, Yb and Lu) resulted in the opposite trend. The superconducting transition temperature and superconducting anisotropy of the grown RE -123 whiskers were 89–93 K and 6–10, respectively. The mixed entropy at the RE site in the RE -123 whiskers did not affect the superconducting transition temperature and superconducting anisotropy.